Computer-aided design for analyzing the influence of anteroposterior translation on artificial knee joint stability. (2022) - Darmanto, D.; Novriansyah, R.; Ismail, R.; Jamari, J.; Bayuseno, A.P.; Anggoro, P.W.
Abstract: The Anteroposterior translational distance (AP) is one of the parameters used to assess stability in the artificial knee joint (AKJ), this translation is influenced by the posterior tibial slope (PTS) and the type of implant. The tibiofemoral contact of the medial pivot system on the AKJ provides satisfaction to the patient, especially for activities that require a deep flexion angle. Asians, especially Indonesians, need a deep flexion angle between 150° and 165° for religious, social, and cultural activities, while patients using artificial knee joint difficulty doing activities with this flexion angle. On the other hand, the development of implant designs with high flexion angles causes a decrease instability because the anteroposterior translation is too large, therefore it is necessary to analyze. This research aims to analyze the stability of AKJ with measurement of AP translation based on computer aided design (CAD) approach. The study used standard existing implants as physical models to develop. The process of reconstruction of physical models begins from surface digitization, surface processing, curve processing, and component improvements. In this study has been successfully tested the stability of AKJ design against AP translation, the results show the level of stability is at the safe limit of medical standards, as well as within the threshold of arthrometers data, so it is expected to provide comfort for religious, social and cultural activities for Asian people, especially in Indonesia.